PREDICTION OF INCREASE IN EARLY MARRIAGE DURING COVID-19 USING THE SINGLE EXPONENTIAL SMOOTHING METHOD - Nasution, Yusuf Ramadhan; Lubis, Solly Ariza; Azis, M. Aldy (UIN Sumatera Utara, 2022)
The Department of Population and Civil Registry of North Sumatra Province must know the prediction of the number of early marriages in the following year so that they can anticipate the occurrence of early marriages. The problem that occurs is that the government through the Department of Population and Civil Registry of North Sumatra Province cannot predict early marriage due to the impact of COVID-19, this is due to the lack of community activity in obtaining knowledge and the difficulty of obtaining information about the occurrence of early marriage. Therefore we need a way that can help the government in predicting early marriage. This study uses single exponential smoothing (SES) to predict an increase in early marriage due to the impact of COVID-19. With the application to predict the increase in marriage due to the impact of COVID-19 using the single exponential smoothing method, it is hoped that the Population and Civil Registry Office of North Sumatra Province will be able to find out the increase in the number of early marriages in the coming period.The Department of Population and Civil Registry of North Sumatra Province must know the prediction of the number of early marriages in the following year so that they can anticipate the occurrence of early marriages. The problem that occurs is that the government through the Department of Population and Civil Registry of North Sumatra Province cannot predict early marriage due to the impact of COVID-19, this is due to the lack of community activity in obtaining knowledge and the difficulty of obtaining information about the occurrence of early marriage. Therefore we need a way that can help the government in predicting early marriage. This study uses single exponential smoothing (SES) to predict an increase in early marriage due to the impact of COVID-19. With the application to predict the increase in marriage due to the impact of COVID-19 using the single exponential smoothing method, it is hoped that the Population and Civil Registry Office of North Sumatra Province will be able to find out the increase in the number of early marriages in the coming period.